Minimal Access Retromandibular Approach to Fractures of Vertical Segment of the Mandible: A Versatile Technique - Munoli, Amarnath V.; Mayekar, Sarika; Mukati, Prachir; Jagannathan, Mukund (Indian Journal of Plastic Surgery, 2024)
Introduction Fractures of the condylar region of the mandible, although fairly common, also generate the most debate regarding management—both closed and open treatment options have been recommended and shown to yield good results. We present our experience with a minimal access retromandibular approach to fractures of the vertical mandible.Materials and Methods This is a retrospective study of all patients who underwent open reduction and internal fixation for fractures of the vertical mandible (condyle, subcondylar region, ramus) using a retromandibular approach at a tertiary care hospital in a metropolitan city in India between January 2022 and July 2023. All fractures were approached using a standard technique through a retromandibular incision and a transparotid route. The proximal segment was mobilized, reduced, and fixed to the ramus with two 2-mm miniplates—one along the posterior border and the other along the sigmoid notch border. Postoperative guiding elastics were placed for 2 weeks without any rigid maxillomandibular fixation. Patients were followed at weekly intervals for 1 month followed by monthly visits for 6 months. At each visit, mouth opening, occlusion, and facial nerve function were assessed. Scar quality was assessed by both examiner and patient using the Patient and Observer Scar Assessment Scale (POSAS) scoring system.Results A total of 25 subcondylar fractures in 20 patients were fixed using the retromandibular approach. Nineteen were male and 1 was female. The etiology of trauma was road accident (8), fall from train (2), fall from height (5) and assault (5). Fifteen patients had unilateral fractures while 5 had bilateral fractures. All patients had concomitant fractures of the mandibular arch which were also fixed. The interval between trauma and surgery ranged from 5 to 28 days. All patients had premature molar contact on the side of fracture with anterior open bite. Mouth opening ranged from 1.5 to 2.5 cm. All the fractures could be fixed using the retromandibular approach. None of the patients developed any facial nerve dysfunction or salivary leak. The occlusion was restored to pretrauma status in all patients and was stable at 6 months' follow-up. Mouth opening ranged from 3.5 to 4 cm. The POSAS observer score ranged from 09 to 19 with a mean score of 12.7. The POSAS patient score ranged from 17 to 28 with a mean score of 20.3 revealing that all patients were extremely happy with the scar.Conclusion The minimal access retromandibular approach to the vertical mandible is a versatile technique enabling accurate reduction and fixation of fractures of the vertical segment of the mandible with good long-term functional and cosmetic results.
Keywords: retromandibular; condylar; condyle fracture; open bite